Community-level reorganizations following migratory pollinator dynamics along a latitudinal gradient. Issue 1930 (1st July 2020) - Magrach, Ainhoa; Lara, Carlos; Luna, Ubaldo Márquez; Díaz-Infante, Sergio; Parker, Ingrid
Abstract : Predicting how communities re-arrange in response to changes in species composition remains a key challenge in ecology. Migratory species, which enter and leave communities across latitudinal gradients, offer us a unique opportunity to evaluate community- and species-level responses to a shift in community composition. We focused on a migratory hummingbird and the communities that host it along a latitudinal and species diversity gradient. Our results show higher niche overlap in more diverse communities, allowing resident species to compensate for the loss of the migrant in providing pollination services. Contrastingly, in less diverse communities, the migrant behaves as a specialist, monopolizing abundant resources. In its absence, its role is not fully covered by resident species, resulting in a decrease in the fruit set of the migrant's preferred plant species. These results help us understand the potential impacts of biodiversity loss and have important implications for community persistence given expected changes in the migratory behaviours of some species.